1998
DOI: 10.1103/physrevb.58.3870
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties and hyperfine parameters of gold–3d-transition-metal impurity pairs in silicon

Abstract: We report theoretical investigations of the chemical trends in the electronic properties of transition-metal impurity pair complexes in a semiconductor. Self-consistent spin-unrestricted electronic state calculations, with a scalar relativistic scheme, in the framework of the multiple-scattering X␣ molecular cluster method, have been carried out for the substitutional gold-3d interstitial transition-metal pairs in silicon in C 3v symmetry. The role played by the 5d and 3d states of the transition metals in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
4
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
5
4
0
Order By: Relevance
“…Figure 1(a) presents the specific case of Mn i in the neutral charge state (3d 7 ). For other TM i impurities in diamond (from Sc to Cu), their t 2 and e levels have an equivalent behavior to those of Mn i , but with a chemical trend such that those levels move all together from the midgap region, in Sc i , toward the valence band, in Cu i , consistent with results for TM i impurities in other semiconductors 25,26 . The 3d-character localization in the TM atomic spheres increases with increasing the atomic number.…”
Section: Resultssupporting
confidence: 75%
“…Figure 1(a) presents the specific case of Mn i in the neutral charge state (3d 7 ). For other TM i impurities in diamond (from Sc to Cu), their t 2 and e levels have an equivalent behavior to those of Mn i , but with a chemical trend such that those levels move all together from the midgap region, in Sc i , toward the valence band, in Cu i , consistent with results for TM i impurities in other semiconductors 25,26 . The 3d-character localization in the TM atomic spheres increases with increasing the atomic number.…”
Section: Resultssupporting
confidence: 75%
“…We have also shown that trends on transition energies, for any of the three sites, could only be rationalized if they were discussed in terms of the increasing occupation of 3d-related states in the bandgap. Such trends are consistent with what would be expected for transition metal impurities in other semiconductors in either isolated configurations 29,30 or forming complexes with other defects 25,31 . Fig.…”
Section: Discussionsupporting
confidence: 78%
“…For the (Ni s N s ) 0 complex, there is a hybridization between 3d-related gap states of Ni s with those 2p-related ones of N s . This indicates a typical covalent interaction between those two impurities 31,32 . Despite this hybridization, the highest occupied energy level in the (Ni s N s ) 0 complex has an e representation, with a prevailing 3d character.…”
Section: Ni-n Complexesmentioning
confidence: 85%
“…This indicates a typical covalent interaction between those two impurities. 35 Despite this hybridization, the highest occupied energy level in the ͑Ni s N s ͒ 0 complex has an e representation, with a prevailing 3d character. On the other hand, for the ͑Ni i N s ͒ 0 complex, the electronic structure results from a weaker interaction between the states of the isolated impurities, more consistent with an ionic model.…”
Section: Ni-n Complexesmentioning
confidence: 98%